PREPARATION AND NUTRITIONAL EVALUATION OF ENRICHED JAM MADE FROM BLENDS OF APPLE, STRAWBERRY AND GRAPES (FUDMA JOURNAL OF SCIENCES, 2024)
The aim of this study is to prepare an acceptable jam from blends of Apple, Strawberry and Grapes. Jams were produced from blends of Apple, Strawberry and Grapes in the following ratios 30:20:10:40 (A= 30g apple, 20g strawberry, 10g grapes and 40g of sugar) and 35:10:15:40 (B= 35g apple, 10g strawberry, 15g grapes and 40g of sugar) respectively. The pulp mixtures were combined with 40g of sugar.  Mixed fruit jam and strawberry jam were used as commercial control labelled as sample C and D respectively. Standard methods were used for the determination of proximate composition, sugar content, phytochemical constituents and sensory evaluation of the Jam. The proximate composition indicated that sample A (15.31±0.12) and B (16.86±0.03) had a moisture content lower than the commercial control C (27.05±0.03) and D (27.60±0.45). The ash, fiber and lipid contents showed no significant difference in the jams produced and the commercial controls. Sample A and B had higher protein 29.58±0.02 and 27.41±0.01 as compared to the commercial controls C and D (24.62±0.02 and 25.15±0.01). No significant (P>0.05) difference was observed in the glucose composition of the sample A and B and the commercial controls C and D. Fructose content in sample A (2.74±0.21) was higher than sample B (1.94±0.01) and the commercial controls C (1.85±0.00) and D (1.42±0.00). Qualitative testing for flavonoids, terpenoids, cardiac glycoside and tannin revealed potential good health benefits. The sensory evaluation revealed that sample A which comprises of 30% apple, 20% strawberry, 10% grapes and 40% sugar was rated best...
Keywords: Jam; Fruits; Proximate Composition; Sensory Evaluation